The Development of ChemicoMine, Maritime Chemistry Comic Webtoon as an Edutainment Media Accordance to the IMO Regulations - Nafillah, Khoirotun; Sari, Dhesi Wulan; Purwanto, Purwanto (Universitas Pendidikan Ganesha, 2024)
Based on the IMO Model Course 7.04 curriculum, chemistry is an introductory course that a candidate for sailor must master. However, most abstract chemistry concepts require technology-based learning media and edutainment. Webtoon is a digital comic that presents the concept of chemistry through real-life visualization strategies to attract student interest. This research aimed to create ChemicoMine, a maritime chemistry comic webtoon whose material content follows IMO regulations. The research method is R&D with the ADDIE model, which is limited to the Development stage. The instruments used in this research were analyst instruments of necessity, the validation tools of storyboard, the instrument validated by an expert in media and material, and the instrument for students. The data analysis techniques used the Likert scale 5. Validation results from an expert in material and media stated that the product received a percentage rating of 87.66% and 95.28% with the category (very good). Student response results obtained percentage of rating of 88.94% with the category (very good). Based on the results, ChemicoMine received a positive student response and can be used as an alternative edutainment media.